2010
DOI: 10.1007/s00127-010-0293-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and subjective burden amongst primary caregivers of people with mental illness in South-Western Nigeria

Abstract: With the high level of psychopathology and burden amongst caregivers in this region, clinicians should be sensitive and review them periodically and to pick up signs of psychopathology which may necessitate attention. Caregivers should be encouraged to meet regularly to share their experiences and ventilate their emotions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…Most research on family care had reported that the caregivers bear the greater burden [14,15]. Many of these researches on caregiver burden were concentrated on caregivers of chronically ill patients such as those with dementia, Alzheimer's disease and heart disease [9,[16][17][18][19]. There seems to be less focus on the wider caregiver roles, especially regarding caregivers of recipients who are not necessarily physically or mentally ill. Also, there is a paucity of research exploring the reactions to care for the elderly person, especially regarding the frail, older members in the household.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on family care had reported that the caregivers bear the greater burden [14,15]. Many of these researches on caregiver burden were concentrated on caregivers of chronically ill patients such as those with dementia, Alzheimer's disease and heart disease [9,[16][17][18][19]. There seems to be less focus on the wider caregiver roles, especially regarding caregivers of recipients who are not necessarily physically or mentally ill. Also, there is a paucity of research exploring the reactions to care for the elderly person, especially regarding the frail, older members in the household.…”
Section: Introductionmentioning
confidence: 99%
“…22 However, cultural views and superstition about mental illness persist in many parts of the country and still affect care of the mentally ill, and by extension also affect the caregiver. Very limited research has been conducted locally on this subject 23,24,25 , and this study will hopefully add to efforts in this area. The investigator's main purpose in the study was to determine the psychological factors, distress and the experience of burden of care among caregivers with the aim of contributing towards planning relevant culturally sensitive interventions to improve the wellbeing of caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Future research should follow up our results since this study has a limited sample and is conducted in a naturalistic northern European context, which might reduce its comparability and the ability to generalize results into other cultural contexts or staff settings [1,34,35]. However, it is worth noticing that patients' directly observable behavioral functioning in the Swedish CLIPS-study already has been shown to be comparable to directly observable behavioral functioning of patients in the United States [36].…”
Section: Discussionmentioning
confidence: 99%